PENTINGNYA KUALITAS KEHIDUPAN KERJA, STRES KERJA, DAN KEPUASAN KERJA DALAM MENINGKATKAN KOMITMEN ORGANISASI GURU [THE IMPORTANCE OF QUALITY OF WORK LIFE, JOB STRESS, AND JOB SATISFACTION IN INCREASING THE ORGANIZATIONAL COMMITMENT OF TEACHERS] - Sinta Mulyani (Jurnal Ketopong Pendidikan, 2021)
Teachers are key in the formal education system. The school as an organization ideally has high committed members, thus avoiding turnover, since the effect of turnover is harmful to the school existence and the students also. This research aims to determine the effect of quality of work life, job stress, and job satisfaction on organizational commitment of the teachers in XYZ Elementary School.  The research using closed questionnaire with Likert scale and the research subjects were 42 teachers. The design used in this study was SEM-PLS with outer model and inner model. The result showed that quality of work life has positive influence to organizational commitment, job stress influenced positively to organizational commitment, and job satisfaction has positive influence to organizational commitment. The research also found that quality of work life has positive influence to job satisfaction, while job stress influenced positively to job satisfaction.